UNVEILING THE MODERATING EFFECT OF TRANSFORMATIONAL LEADERSHIP: HOW CULTURE, CHANGE MANAGEMENT, AND COMMITMENT TO ORGANIZATIONAL PERFORMANCE (Study at UPT Health Development Policy Agency) - Junarti, Junarti; Lestari, Rohmini Indah; Rusdianti, Endang (STIE Pelita Nusantara Semarang, 2024)
Rapid and dynamic changes require every organization to be able to adapt quickly to remain relevant and competitive as an effort to improve organizational performance. This study uses quantitative methods to determine the effect of organizational culture, change management and organizational commitment on organizational performance moderated by transformational leadership. This research was conducted at the UPT of the Health Development Policy Agency, with a total sample of 160 employees. After testing the hypotheses using Multivariate Analysis Structural Equation Model Partial Least Square (SEM-PLS), the research findings revealed that organizational culture and change management have a positive and significant effect on organizational performance, organizational commitment has no significant effect on organizational performance, transformational leadership moderates the relationship of change management to organizational performance but cannot moderate the relationship of organizational culture and organizational commitment to organizational performance. Theoretical and practical implications are examined in this study.